2020
DOI: 10.3390/molecules25184346
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Performance of Benzoxazine Composites for Space Radiation Shielding

Abstract: Innovative multifunctional materials that combine structural functionality with other spacecraft subsystem functions have been identified as a key enabling technology for future deep space missions. In this work, we report the structure and performance of multifunctional polymer matrix composites developed for aerospace applications that require both structural functionality and space radiation shielding. Composites comprised of ultra-high molecular weight polyethylene (UHMWPE) fiber reinforcement and a hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…However, the BN fillers used in these composites suffered from the lack of interfacial adhesion with the HDPE matrix, leading to a limited improvement or even decay of physical and radiation shielding properties of the HDPE/BN composites [26]. Other polymers such as low-density PE (LDPE), epoxy, polystyrene, and polyimide were also considered as the nuclear protective matrices [15,[27][28][29][30]. These studies indicated that general composites are difficult to meet the environmental conditions of radiation, temperature, and mechanics in space at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the BN fillers used in these composites suffered from the lack of interfacial adhesion with the HDPE matrix, leading to a limited improvement or even decay of physical and radiation shielding properties of the HDPE/BN composites [26]. Other polymers such as low-density PE (LDPE), epoxy, polystyrene, and polyimide were also considered as the nuclear protective matrices [15,[27][28][29][30]. These studies indicated that general composites are difficult to meet the environmental conditions of radiation, temperature, and mechanics in space at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their superior performances, PBZs are widely used in the aerospace, defense and transportation industries. [8][9][10][11][12][13][14][15][16][17][18][19][20] However, numerous disadvantages, including brittleness and difficulties in film-forming, limit the range of applications for PBZs.…”
Section: Introductionmentioning
confidence: 99%
“…Polybenzoxazines (PBZs) are attractive composite matrix resins with a number of desirable characteristics, including molecular design flexibility, high thermal stability and so on. Due to their superior performances, PBZs are widely used in the aerospace, defense and transportation industries 8–20 . However, numerous disadvantages, including brittleness and difficulties in film‐forming, limit the range of applications for PBZs.…”
Section: Introductionmentioning
confidence: 99%
“…Benzoxazines are also chemically stable and highly tailorable through reagents, making them suitable for numerous advanced applications. Taking advantage of the versatile molecular design flexibility of benzoxazines, polybenzoxazines specifically designed for space applications have been reported [ 3 , 4 , 5 , 6 ]. The aim of the current paper was to develop a polybenzoxazine-based composite system that is resistant to atomic-oxygen erosion for low-Earth orbital applications.…”
Section: Introductionmentioning
confidence: 99%